1996
DOI: 10.1002/(sici)1097-0304(199612)39:4<396::aid-ccd15>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde left main stenting

Abstract: Percutaneous transluminal coronary angioplasty of protected left main coronary artery stenosis is usually performed by an antegrade approach. In this case report, we describe left main coronary artery stenting by a retrograde approach through a saphenous venous graft in a patient in whom the antegrade approach was considered less appropriate due to chronic ostial occlusion. © 1996 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It was first described by Kahn and Hartzler, who performed balloon angioplasty of a left anterior descending artery CTO via a SVG. In 1996 Silvestri et al reported retrograde stenting of the left main artery through a SVG. In 2006 Surmely et al presented retrograde crossing via septal collaterals, starting the modern era of the retrograde techniques, which can now be performed using septal and epicardial collaterals and aortocoronary bypass grafts .…”
Section: Discussionmentioning
confidence: 99%
“…It was first described by Kahn and Hartzler, who performed balloon angioplasty of a left anterior descending artery CTO via a SVG. In 1996 Silvestri et al reported retrograde stenting of the left main artery through a SVG. In 2006 Surmely et al presented retrograde crossing via septal collaterals, starting the modern era of the retrograde techniques, which can now be performed using septal and epicardial collaterals and aortocoronary bypass grafts .…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous treatment of chronic total occlusions (CTO) using the retrograde approach was first described in the mid 1990s .…”
Section: Introductionmentioning
confidence: 99%
“…8 and 9): [1] antegrade crossing using the ''kissing wire'' or ''just marker'' technique; [2] retrograde true lumen puncture; and [3] various dissection techniques. All techniques require excellent guide support that can be achieved with several methods, such as deep guide catheter intubation, anchor balloon, coaxial anchoring, or use of a mother and child guide catheter technique [36].…”
Section: Crossing the Lesionmentioning
confidence: 99%
“…The retrograde CTO PCI technique was initially described by Kahn and Harzler [1] in 1990 for performing balloon angioplasty of a left anterior descending artery (LAD) CTO via a saphenous vein graft (SVG). In 1996, Silvestri et al [2] reported retrograde stenting of the left main artery via a SVG. The first published reports of retrograde CTO PCI through septal [3][4][5][6][7][8] and epicardial [9] collaterals and arterial bypass grafts [7] appeared in 2006.…”
Section: Introductionmentioning
confidence: 99%